On the Effectiveness of the Improvement of the Top Drive Systems of Drilling Rigs for Rotary Steerable Systems - Ashcheulov, Aleksandr; Kharlamova, Evgeniia (International Journal of Engineering and Technology, 2018)
The article is focused on the improvement of the design of the Russian system of the top drive of the drilling rig for rotary steerable systems through the use of new Russian synchronous electric motors with permanent magnets. Technical advantages are achieved due to the higher efficiency and torque of the drive at partial speeds. The economic efficiency of the new design of the top drive system for rotary steerable systems in different operating modes is estimated.Â